ANTIULCER ACTIVITY OF ELECTROHOMEOPATHIC DRUG (SPAGYRIC ESSENCE) CANCEROUS 15 - 3rd DILUTION AGAINST INDOMETHACIN-INDUCED GASTRIC ULCER IN RATS - SABAT, PRASANT KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: To evaluate the curative protects activity of electrohomeopathic drug Cancerous15 (C15) against Indomethacin (IND)-induced gastric ulcer in albino rats. None of the data have been reported on antiulcer activity of C15 drug. Hence, the present study focuses on the scientific investigation of antiulcer activity of C15 against Indomethacin-induced peptic ulceration of rat models. Methods: A total number of 35 albino rats were divided into five groups equally. Pure water was given to Group 1 (normal). IND was given orally to Group 2 (ulcerated control). Cancerous15 third dilution was given to Group 3. IND was given to Group 4 and Group 5 animals, thereafter pretreatment with Esomeprazole (ESM) and C15-third dilution, respectively. The pretreatments were treated in each day’s interval for 21 days before IND administration. There was provision of food and water throughout the experimental period. On the 23rd day, the stomachs of the sacrificed rats were removed, and (1) ulcer index, (2) percentage of ulcer inhibition, (3) gastric volume, (4) pH, (5) pepsin activity, (6) mucin content, (7) malondialdehyde (MDA) concentration, and (8) stearidonic acid activity were studied. Results: The pre-treated animals with ESM and C15 shown as significantly decreases in ulcer index, gastric volume, pepsin activity and MDA concentration, and significant increase in the percentage ulcer inhibition, pH value, mucin content, and superoxide dismutase activity concentration in comparison to ulcer-induced rats. Conclusion: The study shows the significant ulcer protective activity of the C15 drug against IND-induced peptic ulceration in rats.